Exploring adaptability in long-distance runners: effect of foot strike pattern on lower limb neuro-muscular-skeletal capacity - Garofolini, A. (Victoria University., 2019)
This thesis is an exploration of the controversial hypothesis that a runner`s foot strike pattern defines the demands on the lower extremity, and hence we expect to observe adaptations to its anatomical, mechanical, and neurological function. First, we review the state of the literature to find that long-distance running seems to have an osteogenic and myogenic effect on the foot; however, studies often do not control for foot strike or footwear worn, leading to circumstantial evidence. We therefore aim to determine structural differences between two groups of runners with an antithetical foot strike pattern (habitual rearfoot versus habitual forefoot strikers). We find groups to have similar foot muscle size and to have similar toe flexor strength. Further, we find the trabecular bone volume to be larger in the first metatarsal bone in forefoot strikers; however, the calcaneus reveals no differences between groups in bone density or trabecular structure. We then explore the function of the ankle, in isolation and in coordination with the knee and hip. It appears that habitual forefoot strikers may have access to a wider physiological range of ankle torque and ankle joint angle. This increased potential may allow forefoot strikers to adapt to different footwear by regulating ankle stiffness depending upon motor task. The inter-joint coupling investigation reveals knee-hip coordination pattern of runners to be the most consistent, while ankle-knee couple was the most variable. Forefoot strikers have more variable coordinative patterns than rearfoot strikers irrespective of the footwear worn. We then asked a neuro-mechanical question: Is the control of running kinematics and kinetics influenced by the foot strike type? Using analysis of persistence in time series and analysis of motor redundancy in human movement, we show that rearfoot strikers employ higher active control over critical variables such as limb posture at initial ground contact and leg stiffness. The results suggest that forefoot strikers achieve control of these parameters through exploitation of the abundant degrees of freedom available in the system. Finally, we conclude the thesis with indications for short-term objectives in-line with the research that begun in this thesis.